Aspectos clínicos, histopatológicos e expressão gênica do endométrio de cadelas acometidas por hiperplasia endometrial cística, mucometra e piometra - Voorwald, Fabiana Azevedo [UNESP] (2014)
Hyperplasic and cystic alteration of the canine endometrium compromise reproduction and fertility and may lead to a degenerative inflammation and infection of endometrium. The progressive process usually proposed as the initiating lesion, is mediated by progesterone and potentially aggravated by estrogens. A separate process caused by local uterine irritation to trophoblastic reaction and bacterial proliferation has been recently proposed as an alternate mechanism leading to pyometra. In order to identify molecular similarity and potential targets for therapeutic intervention and biomarkers for endometrium proliferative conditions in humans and dogs, gene expression profiles were performed in fifteen endometrial biopsy samples from female dogs during luteal phase (diestrus), fifteen affected by endometrial cystic hyperplasia, fifteen by mucometra and fifteen by pyometra, and processed on Affymetrix Canine 1.0 ST array. The transcriptome analysis revealed expression of 115, 23 and 284 significantly genes (p<0,05) altered in the hyperplasic compared with normal endometrium, hyperplasic and aseptic secretory compared with hyperplasic endometrium, and infected compared to hyperplasic and aseptic secretory endometrium, respectively. Gene ontology enrichment analysis revealed genes associated with the cell development, growth, proliferation, function and maintenance, and cell-to-cell signaling and interaction were altered in the hyperplasic and proliferative lesion, and also in aseptic secretory endometrium, such as elevated expression of CYR61, EGR1, FOS, GALNT14, IGKC, SLC47A2, IGFBP3, and low expression of ESR2, SOCS3 and MCOLN3. The proliferative to secretory transition revealed genes associated with immune cell trafficking, and cell-mediated immune response, such as FOSB, MAL, CCL4 and SLPI. The infected endometrium due to bacterial infection revealed elevated expression of chemokines (CCL2, CCL3, CXCS), cytokines (IL8, IL6), proteases ...